Legal Culture Hybridity of the South Kalimantan Malay-Chinese in the Division of Inheritance - Firqah Annajiyah Mansyuroh; Ahmadi Hasan; Gusti Muzainah (Pascasarjana UIN ANTASARI Banjarmasin, 2022)
Cultural negotiation is essential because the process always involves conflict and differences. Malay-Chinese is one of the minority groups in South Kalimantan. This study aims to find out how Malay-Chinese culture negotiates differences in the legal culture of inheritance distribution between Chinese customary law, Malay custom, and Islamic law. This research is empirical legal research conducted under an interdisciplinary umbrella. This type of research is field research or research, empirical law. In this study, the author uses a legal sociology approach or practical juridical approach, which is an approach that looks at the legal reality in society, and a legal anthropological approach. The research findings show that Malay-Chinese negotiates differences in Islamic values and religion by choosing or combining the two cultural values. The negotiation process is carried out by applying cultural values as they are ethnic and adapt to the cultural values of Malay Islam. This cultural negotiation process then builds a hybrid Malay-Chinese identity. Resistance, their hybridity is used to survive and to fight the dominant Malay Islamic cultural values.